Potassium use efficiency of upland rice genotypes - Fageria, Nand Kumar (Pesquisa Agropecuaria Brasileira, 2000)
Use of nutrient efficient cultivar in crop production is an important strategy in reducing cost of crop production. A greenhouse experiment was conducted at the Embrapa-Centro Nacional de Pesquisa de Arroz e Feijão, Experimental Station of Capivara, Santo Antonio de Goiás, Brazil, to study the efficiency of 15 genotypes of upland rice (Oryza sativa L.) at low (without K application) and high (application of 200 mg kg-1 of K) levels of K applied in the soil. Genotypes differed significantly in relation to grain yield and K use efficiency. Based on grain yield at low K level and agronomic efficiency of K use, genotypes were classified as efficient and unefficient. Genotypes Rio Paranaíba, L141 and Guarani were classified as efficient and responsives. Second most important group of the genotypes was efficient and non-responsive. Genotypes CNA6187, CNA7911 and CNA7680 fall in this category.